Celebrating 15 years. Issue 5 (October 2016) - Yeoman, Ian
Abstract 15th anniversary edition of theJournal of Revenue & Pricing Management was launched a seminar led by Dr Ian Yeoman (Victoria University) and David Meaclem (Air New Zealand) at Victoria University of Wellington The edition included contributions from leading academics and practitioners including Peter Belobaba (MIT), Sherri Kimes (Cornell), Ben Vinod (Sabre) and Dax Cross (Revenue Analytics) highlighting a number of themes that have brought about the evolution of Revenue Management.